1993
DOI: 10.1001/archsurg.1993.01420180085016
|View full text |Cite
|
Sign up to set email alerts
|

Cause of Death in Multiple Endocrine Neoplasia Type 1

Abstract: It is concluded that MEN-1 leads to premature death, and that neoplasia rather than peptic ulcer disease is the main cause of death. Deaths from pituitary tumor or malignant endocrine tumors within the thorax were just as common or more common than deaths from pancreatic malignant neoplasms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
159
3
2

Year Published

1998
1998
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 143 publications
(180 citation statements)
references
References 10 publications
16
159
3
2
Order By: Relevance
“…In series focusing on MEN1-related mortality, 5-9% of the MEN1-related deaths occurring before 1990 were attributed to pulmonary carcinoids (Wilkinson et al 1993, Goudet et al 2010, with no deaths due to pulmonary carcinoids reported after 1990 (Geerdink et al 2003, Wilson et al 2008, Goudet et al 2010. In line with these findings, pulmonary carcinoids do not give an increased risk of death in MEN1 patients (Goudet et al 2010).…”
Section: Natural History and Prognostic Factors: Pulmonary Carcinoidsmentioning
confidence: 59%
“…In series focusing on MEN1-related mortality, 5-9% of the MEN1-related deaths occurring before 1990 were attributed to pulmonary carcinoids (Wilkinson et al 1993, Goudet et al 2010, with no deaths due to pulmonary carcinoids reported after 1990 (Geerdink et al 2003, Wilson et al 2008, Goudet et al 2010. In line with these findings, pulmonary carcinoids do not give an increased risk of death in MEN1 patients (Goudet et al 2010).…”
Section: Natural History and Prognostic Factors: Pulmonary Carcinoidsmentioning
confidence: 59%
“…In these studies, deaths from malignant pancreatic islet cell tumours account for only 9-13% of the deaths related to MEN-1. Wilkinson et al (26) were the first to conclude that neoplasm rather than peptic ulcer disease is the main cause of death in MEN-1. Other recent studies (10,27,28) have confirmed this conclusion.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, histopathological analysis of resected MEN1-pancreases has shown numerous micro-tumors that were not identified using imaging studies (Anlauf et al 2006), further emphasizing the diffuse involvement of the pancreas in patients with MEN1. Historically, NF tumors were diagnosed late because of local symptoms and were associated with a high lethality early in life (Wilkinson et al 1993, Doherty et al 1998, Goudet et al 2010, Ito et al 2013). Indeed, the mean age of death for patients who died because of NF-pNET was 43 in a previous registry-based study (comprising patients diagnosed with MEN1 in France from 1956 to 2003) and 46 in the study by Doherty and coworkers analyzing patients registered in the Washington University database (Doherty et al 1998).…”
Section: Non-functional Pancreatic Netsmentioning
confidence: 99%